Penguatan Pendidikan Karakter Siswa Melalui Tujuh Kebiasaan Anak Indonesia Hebat di SMK Negeri 3 Pekanbaru - Amelia Agustina; Edi Ismanto (Jurnal Pendidikan Dirgantara, 2025)
Character education is one of the important aspects in forming a good personality in each individual. Good character will have a positive impact on the social, emotional, and academic life of students. The 7 Habits of Great Indonesian Children Movement Program is designed as a strategic step to form individuals who are not only academically intelligent, but also have strong characters that are the foundation of the nation's success in the future. The main objective of this movement is to create a golden generation of Indonesia in 2045. By instilling positive habits from an early age, it is hoped that Indonesian children can grow into healthy, intelligent, characterful individuals who contribute positively to the nation and state. One of the State Vocational Schools in Pekanbaru has implemented the 7 habits of great Indonesian children movement, namely at State Vocational School 3 Pekanbaru.